La Crosse Encephalitis in Children - McJunkin, James E; de los Reyes, Emily C; Irazuzta, Jose E; Caceres, Manuel J; Khan, Raheel R; Minnich, Linda L; Fu, Kai D; Lovett, Gretchen D; Tsai, Theodore; Thompson, Ann (The New England journal of medicine, 2001)
La Crosse virus is the most pathogenic member of the California encephalitis serogroup. It was first isolated from the brain of a four-year-old child who had died of “rural encephalitis” in La Crosse County, Wisconsin. 1 The virus is transmitted by the tree-hole mosquito, Aedes triseriatus, and causes the most prevalent arboviral infection in children in North America. 1 – 7 Nevertheless, La Crosse encephalitis often goes unrecognized. The virus typically cannot be recovered from cerebrospinal fluid, and the disease can masquerade as enteroviral meningitis when mild and as herpes simplex encephalitis when severe. 8 – 14 Currently, there is no antiviral therapy that has . . .